If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+7+13=5X-1
We move all terms to the left:
X+7+13-(5X-1)=0
We add all the numbers together, and all the variables
X-(5X-1)+20=0
We get rid of parentheses
X-5X+1+20=0
We add all the numbers together, and all the variables
-4X+21=0
We move all terms containing X to the left, all other terms to the right
-4X=-21
X=-21/-4
X=5+1/4
| 4+3d=4+3d+10d | | x+(x+2)=94 | | 9a-4=3(3a-4) | | 2x-8=-5x+20 | | -t/4-4=3.1 | | 4.3(-2.1)=z | | 2.5x-3.5+5.1x=3+1.7x | | u-188=264 | | 3/4x+6=3/4(8+x) | | X+3+3x=8x-6 | | -2q+5=2q+1 | | -3(88x-87)+92=90 | | 2x-8=5x+20 | | 50+2.3x=102.2+3.5x | | z+10=14 | | 4x(x-1)=4x-5 | | 12=18-6n | | -28x-14+17x=52 | | z/1=20 | | 7(x-2)=64 | | h/6-2=8.4 | | 7-h=-2h | | 8p-9=5p-5 | | –7y=–4−8y | | 4x+16=4x-12 | | -10+4j=-6j+10 | | 7+x+9=5x+7 | | 5x/2+x=9+3x+10 | | 3p+27=-15 | | -15x(7-1=0 | | 102x-119=17(6x-7) | | 5+14x=3x |